Semi-conductors faults analysis in dual active bridge DC-DC converter - Airabella, Andres Miguel (2016)
Failures in power semi-conductors of a dual active bridge converter are characterised considering open-circuit faults in diodes and transistors. A detailed electrical waveforms analysis to identify the main symptoms of the converter during normal and failure conditions is presented. Based on this analysis, a fault diagnosis strategy is proposed which is able to identify failures either in a diode or in a transistor as well as its location in the circuit. Finally, simulation and experimental results, using a prototype of 1 KW, are presented in this study to demonstrate the practical feasibility of the theoretical proposal.